Efektivitas Probiotik Lactobacillus plantarum 2C12 dan Lactobacillus acidophilus 2B4 Sebagai Pencegah Diare pada Tikus Percobaan - I I Arief; B Sri Laksmi Jenie; M Astawan; A B Witarto (Media Peternakan, 2010)
The aim of this study was to evaluate the effectiveness of probiotics Lactobacillus plantarum 2C12 and Lactobacillus acidophilus 2B4 to prevent diarrhea caused by enteropathogenic Escherichia coli (EPEC). Albino rats (Rattus norvegicus) were daily orally administered by 108 cfu/ml of both probiotics without or simultaneously infected with EPEC (106 cfu/ml) for 7 days. Negative control was not infected by probiotic and EPEC while positive control was challenged with EPEC alone. After 1, 2 and 3 weeks, total of lactic acid bacteria (LAB) and E. coli of mucosa of cecum and cecum content were evaluated.  It was observed that rats administered by L. plantarum 2C12 and L. acidophilus 2B4 and challenged with EPEC had better performances when compared with the positive control for daily weight gain, feed consumption, feed efficiency rate. Diarrhea was determined by total of E. coli on cecum and watery fecal. Both probiotics could increase 1 log10 cfu/cm2 of total LAB on mucosa of cecum and also 1 log10 cfu/g of cecum content. Both probiotics also could reduce 1-3 log10 cfu/cm2 population of E.coli on mucosa of cecum and 1 log10 cfu/g of cecum content. L. plantarum 2C12 and L. acidophilus 2B4 were effective as probiotics against EPEC on rats.